The Impact of Live Streaming Commerce and Online Reviews on Impulsive Buying with E-Trust as an Intervening Variable for Somethinc Cosmetics Among Generation Z - Siti Nurul Nazwa; Meitiana; Vivy Kristinae; Roby Sambung (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study investigates the influence of live streaming commerce and online customer reviews on impulsive buying behavior, with e-trust as an intervening variable, focusing on Somethinc cosmetics among Generation Z consumers. Utilizing a quantitative approach, the research gathered data from 100 respondents selected through purposive sampling in Palangka Raya City. The Partial Least Square - Structural Equation Model (PLS-SEM) was employed to analyze the relationships between variables. The findings reveal that live streaming commerce has a significant positive effect on both e-trust and impulsive buying, emphasizing its role as an interactive and engaging marketing tool. Online customer reviews also positively impact e-trust and impulsive buying, albeit with a weaker effect. However, the mediating role of e-trust between these factors and impulsive buying is not statistically significant, suggesting that Generation Z consumers prioritize interactive and social aspects over trust in their purchasing decisions. This study provides valuable insights for marketers aiming to enhance impulsive buying through digital marketing strategies. Future research is encouraged to explore these relationships across various industries and demographics to broaden the understanding of impulsive buying behavior.